ECONOMIC ASPECTS OF BANK MARKETING AND THE REAL SECTOR - Uteubayeva Ainur Talgatovna; Kabiyev Ansar Amangeldyevicch; Imangaliyeva М. (Academic Journal of Physical and Chemical Sciences, 2020)
In an era of rapid technological development and increasing competition, the value of the mass customer as a source of profit is growing steadily. The client becomes the main asset of the bank, its needs and requirements are in the focus of the banking business. The survival strategy in the struggle for the mass customer is based on the submission of all business processes and procedures to one single goal – customer satisfaction. In the future, business performance will be determined by the degree of customer satisfaction. The economic crisis, the crisis of industrial production is pushing for a review of key aspects of banking marketing, which should explore the interaction of the industrial and banking sectors and generate solutions to increase the effectiveness of their interaction. The crisis confirms that it is necessary to improve the tools of banking marketing in the industrial sector of the economy of the region. Computer models, where the atoms are agents, are called agentbased models. In most works devoted to the construction and study of agent-based models, the rules for interaction between agents are extremely simple. Nevertheless, the result is quite meaningful meaningful results. The issues of improving the use of bank marketing tool to improve the efficiency of interaction between the industrial and banking sectors of the economy are considered. Reasoning upon the economic aspects of the effectiveness of bank marketing, the authors state that a marketing performance evaluation system should have not only mechanisms for a posteriori analysis (that is, analysis of the results of acceptance or rejection of an offer), but also possibility of priori assessment of marketing offers, campaigns, profitability, and even marketing budgets. The system should contain a tool that simulates the appearance of clients, the selection of offers to clients and assessing the acceptance or rejection of offers, probable consumption or non-consumption of the proposed product